Everolimus long-term use in patients with tuberous sclerosis complex: Four-year update of the EXIST-2 study. - John J Bissler; J Chris Kingswood; Elzbieta Radzikowska; Bernard A Zonnenberg; Elena Belousova; Michael D Frost; Matthias Sauter; Susanne Brakemeier; Petrus J de Vries; Noah Berkowitz; Maurizio Voi; Severine Peyrard; et al. (PLoS ONE)
Objectives We examined the long-term effects of everolimus in patients with renal angiomyolipoma associated with tuberous sclerosis complex or sporadic lymphangioleiomyomatosis. Methods Following favorable results from the double-blind core phase of EXIST-2 (NCT00790400), patients were allowed to receive open-label everolimus (extension phase). Patients initially randomly assigned to everolimus continued on the same dose; those who were receiving placebo crossed over to everolimus 10 mg/day. Dose modifications were based on tolerability. The primary end point was angiomyolipoma response rate, defined as a ≥50% reduction from baseline in the sum volume of target renal angiomyolipomas in the absence of new target angiomyolipomas, kidney volume increase of >20% from nadir, and angiomyolipoma-related bleeding grade ≥2. The key secondary end point was safety. Results Of the 112 patients who received ≥1 dose of everolimus, 58% (95% CI, 48.3% to 67.3%) achieved angiomyolipoma response. Almost all patients (97%) experienced reduction in renal lesion volumes at some point during the study period. Median duration of everolimus exposure was 46.9 months. Sixteen (14.3%) patients experienced angiomyolipoma progression at some point in the study. No angiomyolipoma-related bleeding or nephrectomies were reported. One patient on everolimus underwent embolization for worsening right flank pain. Subependymal giant cell astrocytoma lesion response was achieved in 48% of patients and skin lesion response in 68% of patients. The most common adverse events suspected to be treatment-related were stomatitis (42%), hypercholesterolemia (30.4%), acne (25.9%), aphthous stomatitis and nasopharyngitis (each 21.4%). Ten (8.9%) patients withdrew because of an adverse event. Renal function remained stable, and the frequency of emergent adverse events generally decreased over time. Conclusions Everolimus treatment remained safe and effective over approximately 4 years. The overall risk/benefit assessment supports the use of everolimus as a viable treatment option for angiomyolipoma associated with tuberous sclerosis complex or sporadic lymphangioleiomyomatosis. Trial registration ClinicalTrials.gov NCT00790400.